Bahasa Indonesia pada Era Kolonial Hingga Reformasi - Alya Nataly; Ayu Nadira Wulandari; Harry Situmeang; Sonia Matanari (Departement of Mathematics Education, 2024)
The aim of this research is to find out how the Indonesian language was used during the Dutch colonial period until now, where the early history of the Indonesian language was born from the Malay language which then grew and developed so that Indonesian became the unified language of the Republic of Indonesia. It is also known about the struggles of educated youth in taking the youth oath using Indonesian as an intermediary, the use of Indonesian during the Old Order era which was used in various political situations such as making the youth oath, the legal basis in the form of the constitution. So the use of Indonesian developed during the New Order era where a standardized language would make it easier for everyone to communicate by changing the form of writing from the Suwandi EYD spelling to the reformed use of Indonesian until now where as the official language Indonesian is used as the language of instruction. In educational institutions, data even shows that at least 52 foreign countries have opened Indonesian language programs and this development will continue to increase with evidence of the formation of language centers.